RANCANG BANGUN GAME STOCK STREET SAGA BERDASARKAN ANALISIS TEKNIKAL - Tristiyanto; Yuliyanto, Kurniawan Dwi; Syarif, Admi; Wulansari, Ossy Endah Dwi (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2024)
This research focuses on the development of the "Stock Street Saga" game, which effectively integrates technical analysis concepts using indicators such as volume, momentum, trend, and oscillator. The game is designed to provide a simulation that allows players, especially beginners, to practice and understand technical analysis without financial risk. The research utilized the Game Development Life Cycle (GDLC) method, ensuring a systematic approach from initiation to production and testing. User Acceptance Testing (UAT) results from 40 respondents, consisting of novice traders and game developers, showed that the game effectively facilitates learning technical analysis. With an average UAT score of 75.57%, it indicates that the game meets the criteria of being a good educational tool, successfully implementing technical analysis concepts and offering an effective learning experience